2009
DOI: 10.1007/s11069-009-9412-1
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction hazard mapping at the town of Edessa, Northern Greece

Abstract: The town of Edessa is located on Northern Greece at a region that is characterized as low seismicity zone due to the fact that few moderate events of M \ 6 occurred during the last century. According to the Greek Seismic Code, the expected acceleration having a 10% probability of being exceeded in 50 years is equal to 0.16g. However, an amplification of ground motion is likely to occur due the local geology that is consisted of Holocene fluvio-torrential deposits. The basic aim of this paper is to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Thus, we concluded that the proposed value of PGA, 0.16g, by the EAK (2000) is not representative for a "microzonation" study and we decided to perform 1-D site response analysis using data provided by seven borings with SPT. In order to achieve this, several real acceleration time histories were selected with respect to the type of causative fault, the magnitude of the earthquake and the geological conditions at the recorded station, and were downloaded by the web site of European Strong motion Database (ESD) www.isesd.cv.ic.ac.uk/ESD (Papathanassiou and Valkaniotis, 2009). …”
Section: Edessamentioning
confidence: 99%
“…Thus, we concluded that the proposed value of PGA, 0.16g, by the EAK (2000) is not representative for a "microzonation" study and we decided to perform 1-D site response analysis using data provided by seven borings with SPT. In order to achieve this, several real acceleration time histories were selected with respect to the type of causative fault, the magnitude of the earthquake and the geological conditions at the recorded station, and were downloaded by the web site of European Strong motion Database (ESD) www.isesd.cv.ic.ac.uk/ESD (Papathanassiou and Valkaniotis, 2009). …”
Section: Edessamentioning
confidence: 99%